Characterizing a novel scintillating glass for application to megavoltage cone‐beam computed tomography. Issue 3 (14th February 2019) - Hu, Yue‐Houng; Shedlock, Daniel; Wang, Adam; Rottmann, Joerg; Baturin, Paul; Myronakis, Marios; Huber, Pascal; Fueglistaller, Rony; Shi, Mengying; Morf, Daniel; Star‐Lack, Josh; Berbeco, Ross I.
Abstract : Purpose: The purpose of this study was to evaluate the performance of a prototype electric portal imaging device (EPID) with a high detective quantum efficiency (DQE) scintillator, LKH‐5. Specifically, image quality in context of both planar and megavoltage (MV) cone‐beam computed tomography (CBCT) is analyzed. Methods: Planar image quality in terms of modulation transfer function (MTF), noise power spectrum (NPS), and DQE are measured and compared to an existing EPID (AS‐1200) using the 6 MV beamline for a Varian TrueBeam linac. Imager performance is contextualized for three‐dimensional (3D), MV‐CBCT performance by measuring imager lag and analyzing the expected degradation of the DQE as a function of dose. Finally, comparisons between reconstructed images of the Catphan phantom in terms of qualitative quality and signal‐difference‐to‐noise ratio (SDNR) are made for 6 MV images using both conventional and LKH‐5 EPIDs as well as for the kilovoltage (kV) on‐board imager (OBI). Results: Analysis of the NPS reveals linearity at all measured doses using the prototype LKH‐5 detector. While the first zero of the MTF is much lower for the LKH‐5 detector than the conventional EPID (0.6 cycles/mm vs 1.6 cycles/mm), the normalized NPS (NNPS) multiplied by total quanta (qNNPS) of the LKH‐5 detector is roughly a factor of seven to eight times lower, yielding a DQE(0) of approximately 8%. First, second, and third frame lag were measured at approximately 23%, 5%, and 1%, respectively, although no noticeable image artifacts were apparent in reconstructed volumes. Analysis of low‐dose performance reveals that DQE(0) remains at 80% of its maximum value at a dose as low as 7.5 × 10 −6 MU. For a 400 projection technique, this represents a total scan dose of 0.0030 MU, suggesting that if imaging doses are increased to a value typical of kV‐CBCT scans ( 2.7 cGy), the LKH‐5 detector will retain quantum noise limited performance. Finally, comparing Catphan scans, the prototype detector exhibits much lower image noise than the conventional EPID, resulting in improved small object representation. Furthermore, SDNR of H2 O and polystyrene cylinders improved from −1.95 and 2.94 to −15 and 18.7, respectively. Conclusions: Imaging performance of the prototype LKH‐5 detector was measured and analyzed for both planar and 3D contexts. Improving noise transfer of the detector results in concurrent improvement of DQE(0). For 3D imaging, temporal characteristics were adequate for artifact‐free performance and at relevant doses, the detector retained quantum noise limited performance. Although quantitative MTF measurements suggest poorer resolution, small object representation of the prototype imager is qualitatively improved over the conventional detector due to the measured reduction in noise.